Improving the pre-service teachers’ academic learning achievement in educational research class and self-regulation with self-assessment approaches - Tiyawongsuwan, Siripan (Kasetsart Journal of Social Sciences, 2021)
The relationship of self-assessment approaches on academic learning achievement and self-regulation has been extensively explored but the impact for pre-service teachers has not been thoroughly examined, even in research courses where instruction is often neglected. This article reports an empirical investigation of the effectiveness of selfassessment approaches on pre-service teachers’ academic learning achievement in educational research class and self-regulation. A quasi-experimental pretest-posttest control group design was adopted in this study. The participants were 43 pre-service teachers enrolled in the first semester of 2018 of an educational research course. Data were collected using a comprehensive research learning test, subsequent tests, and self-regulation questionnaire. Data were analyzed by using arithmetic mean, standard deviation, sample independent t-test, and paired sample t-test. The result revealed that self-assessment approaches have a positive effect on academic learning achievement and self-regulation. The percentage points on quizzes of the experimental group showed an increase in the following quizzes. The results demonstrated the improvement of pre-service teachers who completed the self-assessment training.